Migration and wintering patterns of Golden Plover, Pluvialis apricaria, in the Northern part of Modena province (Northern Italy) - Carlo Giannella; Raffaele Gemmato (Rivista Italiana di Ornitologia - Research in Ornithology, 2012)
The authors present the results on the migration and wintering patterns of Golden Plover. There are differences on biometrics between juv (immature)/adults. The juv are mainly significantly present in autumn and the adults in spring migration. We found a significant differences in the weights with adults weighing much more than young ones perhaps demonstrating a different migration pattern.